Fluorinated PLGA-PEG-Mannose Nanoparticles for Tumor-Associated Macrophage Detection by Optical Imaging and MRI - Zambito, Giorgia; Deng, Siyuan; Haeck, Joost; Gaspar, Natasa; Himmelreich, Uwe; Censi, Roberta; Löwik, Clemens; Di Martino, Piera; Mezzanotte, Laura (Frontiers in Medicine, 2021)
Tumor-associated macrophages (TAMs) promotes cancer growth and metastasis, but their role in tumor development needs to be fully understood due to the dynamic changes of tumor microenvironment (TME). Here, we report an approach to visualize TAMs by optical imaging and by Fluorine-19 (19F) magnetic resonance imaging (MRI) that is largely applied to track immune cells in vivo. TAMs are targeted with PLGA-PEG-mannose nanoparticles (NPs) encapsulating PFCE as MRI contrast agent. These particles are preferentially recognized and phagocytized by TAMs that overexpress the mannose receptor (MRC1/CD206). The PLGA-PEG-mannose NPs are not toxic and they were up-taken by macrophages as confirmed by in vitro confocal microscopy. At 48 h after intravenous injection of PLGA-PEG-mannose NPs, 4T1 xenograft mice were imaged and fluorine-19 nuclear magnetic resonance confirmed nanoparticle retention at the tumor site. Because of the lack of 19F background in the body, observed 19F signals are robust and exhibit an excellent degree of specificity. In vivo imaging of TAMs in the TME by 19F MRI opens the possibility for detection of cancer at earlier stage and for prompt therapeutic interventions in solid tumors.